2003
DOI: 10.1073/pnas.2035256100
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of site-specifically acetylated and methylated histone proteins: Reagents for evaluation of the histone code hypothesis

Abstract: The functional capacity of genetically encoded histone proteins can be powerfully expanded by posttranslational modification. A growing body of biochemical and genetic evidence clearly links the unique combinatorial patterning of side chain acetylation, methylation, and phosphorylation mainly within the highly conserved N termini of histones H2A, H2B, H3, and H4 with the regulation of gene expression and chromatin assembly and remodeling, in effect constituting a ''histone code'' for epigenetic signaling. Deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
109
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 31 publications
0
109
0
4
Order By: Relevance
“…Various synthesized histone N-terminal peptides, containing particular site-specific modifications, were then ligated to recombinantly produced histone C-terminal globular domains containing an engineered N-terminal cysteine residue. Those authors showed that the synthetic histones generated by this method are fully functional, as verified by the self-assembly into higher-order heterotetramers, their deposition into nucleosomes by chromatin assembly/remodeling factors, and enzymatic modifications (162). Such a method, combined with mass spectrometry and amino acid exchange analysis of potential target proteins, could be utilized for studies of poly-ADP ribosylation.…”
Section: Pargsmentioning
confidence: 96%
See 1 more Smart Citation
“…Various synthesized histone N-terminal peptides, containing particular site-specific modifications, were then ligated to recombinantly produced histone C-terminal globular domains containing an engineered N-terminal cysteine residue. Those authors showed that the synthetic histones generated by this method are fully functional, as verified by the self-assembly into higher-order heterotetramers, their deposition into nucleosomes by chromatin assembly/remodeling factors, and enzymatic modifications (162). Such a method, combined with mass spectrometry and amino acid exchange analysis of potential target proteins, could be utilized for studies of poly-ADP ribosylation.…”
Section: Pargsmentioning
confidence: 96%
“…their amino-terminal histone tails (162). Those authors synthesized peptide thioesters corresponding to histone N termini.…”
Section: Pargsmentioning
confidence: 99%
“…To examine the precise role of Lys acetylation at the nucleosome dyad, we generated nucleosomes bearing acetylated Lys on histone H3-K115 and/or H3-K122 by expressed protein ligation (25)(26)(27). We found that the nucleosome position was not altered by H3-K115 and/or H3-K122 acetylation.…”
mentioning
confidence: 99%
“…Clearly, this represents a successful example for installing methyl group to the lysine residues in the N-terminal regions of the core histones. In addition to its use in studying H3K9 methylation, the NCL strategy was utilized to generate several other homogeneously modified histones, including H4 with K16 acetylation, 190 H4 with K5, 8 or 12 acetylations, 189 and H3 with S10 phosphorylation. 191 These examples illustrate that NCL is a robust tool to address the PTMs occurring on the Nterminal tails.…”
Section: Adding Methylation Marks To the Amino-termini Of Histones Usmentioning
confidence: 99%
“…This is especially challenging for histone synthesis or semisynthesis because almost no cysteine residues are present in histones (the only one is H3 Cys110). Use of auxiliary groups [201][202][203] or desulfurization after the ligation reaction 189,204,205 has been shown by several groups to expand NCL reactions beyond cysteine. In applying NCL for selective labeling of a recombinant protein, certain intrinsic properties of the protein target may be affected.…”
Section: Limitations Of Nclmentioning
confidence: 99%